Korelasi Kemampuan Berbahasa Arab dengan Hasil Belajar Mata Pelajaran Al-Qur’an Hadits - Rizki Septiana; Khairil Anwar; Muhammad Singgih (Al Mitsali, 2021)
Arabic is a Semitic language originating from the Middle East region which is used as the mother tongue of several countries. Arabic has a close relationship with Islam because the Al-Qur'an, Hadith, and the books of the majority of scholars are in Arabic, so it is very important to learn Arabic to be able to understand the Al-Qur'an and Hadith. This type of research is a quantitative correlation by utilizing data in the form of student report cards to find out how much the relationship between Arabic language skills and learning outcomes of Al-Qur'an Hadith subjects. The two variables are processed into classified data which is then used as a correlation map. From the correlation map, the correlation index value can be known as well as determining the interpretation of the correlation index value. After the report card scores were analyzed, it was found that the average Arabic language ability of students was 88.67 and the average value of learning outcomes of Al-Qur'an Hadith subjects was 93.50. This indicates that students' Arabic language skills are fairly good and the learning outcomes of Al-Qur'an Hadith subjects are very good. The next step is that the correlation map is analyzed, it is found that the correlation index value is 0.59 or> 0, which means that there is a positive correlation between Arabic language skills and learning outcomes of Al-Quran Hadith subjects. Finally, giving an interpretation number to the correlation index value based on the table. The positive correlation between Arabic language skills and Al-Qur'an Hadith learning outcomes is a moderate positive correlation. From this research, it is hoped that teachers can increase creativity in teaching so that students can improve their Arabic language skills and learning outcomes, especially in the subjects of Al-Qur'an and Hadith.